Леся Українка та Марія Конопніцька - Маланій, Олена; Malanii, Olena (Східноєвропейський національний університет імені Лесі Українки, 2016)
Статтю присвячено україно-польським взаєминам, впливам та взаємовпли- вам і доведено актуальність проблеми «Леся Українка та польська література». Зокрема розглянуто творчість неординарних і самобутніх письменниць – Марії Конопніцької та Лесі Українки, перегукам і паралелям їхньої спадщини. З’ясо- вано тісний взаємозв’язок і прозорість основних тенденцій творчого шляху обох письменниць, виявлено спільність джерельної бази, мотивів, тем і проблем у їхній поезії, прозі та драматургії. The article is devo- ted to the Ukrainian-Polish cultural relations, mutual influence, it proved the relevance of the problem of “Lesia Ukrainka and Polish literature”. In particular, work is con- sidered unconventional and original writers – Maria Konopnitska and Lesia Ukrainka, echoes and parallels their artistic heritage. It was found a close relationship and trans- parency of the main trends of the creative ways the two writers, found common source base, motifs, themes and problems in their poetry, prose and drama. Obviously there are common interests in different literary genres in use-character images, sound civil motives writers. Traces the internal and external relationships creativity of Lesia Ukrainka and Maria Konopnitska with the political and cultural processes at the turn of the nineteenth and twentieth centuries, writers sremlenie to the modernization of Russian literature.
Lesіa Ukrainka and Maria Konopnitska
Keywords: польська література; Леся Українка; Марія Конопніцька; літературна критика; творчі паралелі; світоглядні концепти творчості; Polish Literature; Lesia Ukrainka; Maria Konopnitska; literary criticism; creative parallels ideological concepts creativity